CHANGES IN THE PATTERN OF INTERNATIONAL ECONOMIC DIPLOMACY CASE STUDY: FOREIGN INVESTMENT IN INDONESIA - Diah Apriliani (Indonesian Research of Sustainability Management, Business, & Administration (IRHAMNA), 2025)
This article explains that changes in the pattern of international economic diplomacy occur due to the awareness of 'developing countries' in carrying out relations between countries within the wider community. This review is solely based on secondary data collected from previous journals using literature studies. The high level of globalization and modern technology makes the movement of money between continents quite fast and cheap. Investors are looking for investment-friendly destinations to invest big enough and accumulate a great return on investment. Over the years, Indonesia has developed into an attractive hub for business people from all corners of the world and a magnet for foreign direct investment.